The Relationship Between the Duration of Hemodialysis and Stress Levels in Chronic Kidney Disease Patients in the Hemodialysis Ward of Dr. Sitanala General Hospital - Nada Puspita; Destiawan Eko Utomo; Cicirosnita J. Idu (Jurnal Vokasi Kesehatan, 2026)
Introduction: Chronic kidney disease is a health problem that occurs globally as well as in Indonesia, with a prevalence that increases every year, characterized by a gradual decline in kidney function. Objective: This study aims to determine the relationship between the duration of undergoing hemodialysis and stress levels in patients with chronic kidney disease in the hemodialysis unit of RSUP Dr. Sitanala. Methods: This study used a descriptive analytic method with a cross-sectional approach. The sampling technique used total sampling, with a total of 88 respondents who routinely undergo hemodialysis therapy in the hemodialysis unit of RSUP Dr. Sitanala. Data were analyzed using the Spearman Rank test to assess correlations between variables. Results: The results showed that the majority of patients had undergone hemodialysis for <12 months (52.3%), while most patients experienced stress at a moderate level (43.2%). The Spearman Rank test showed a significant relationship between the duration of hemodialysis and stress levels (p-value = 0.000) with an r value of 0.461. Conclusion: The study shows that there is a relationship between the duration of undergoing hemodialysis and stress levels. Patients who have undergone therapy for <12 months are more prone to stress due to the unfulfilled stage of self-acceptance. Therefore, this study emphasizes the importance of focusing on the psychological condition of patients experiencing stress during hemodialysis.